Monk's Hood : the third chronicle of Brother Cadfael, of the Benedictine Abbey of Saint Peter and Saint Paul, at Shrewsbury - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael, 2014)
Gervase Bonel is a guest of Shrewsbury Abbey of Saint Peter and Saint Paul when he suddenly takes ill. Luckily, the abbey boasts the services of the clever and kindly Brother Cadfael, a skilled herbalist. Cadfael hurries to the man's bedside, only to be confronted with two surprises: In Master Bonel's wife, the good monk recognizes Richildis, whom he loved before he took his vows--and Master Bonel has been fatally poisoned by monk's-hood oil from Cadfael's stores. The sheriff is convinced that the murderer is Richildis's son, Edwin, who hated his stepfather. But Cadfael, guided in part by his concern for a woman to whom he was once betrothed, is certain of her son's innocence.